Garis panduan penyediaan perintah S.129 PDPA 2010 (cross-border data transfer under s.129 of the PDPA 2010) - Zulhuda, Sonny (2016)
According to section 129 of the Personal Data Protection Act (PDPA) 2010, a data user shall not transfer any personal data of a data subject to a place outside Malaysia unless to such place as specified by the Minister, upon the recommendation of the Commissioner, by notification published in the Gazette. In view of this, the office of the PDP Commissioner wishes to issue a Ministerial order to specify those places. This briefing is called to enlighten the government on several key issues that need to be addressed when preparing such order.